Employability skills in mainstream education: Innovations in schooling and institutional isomorphism. (14th July 2021) - Robson, James; Randhawa, Ashmita; Keep, Ewart
Abstract : In England, the Studio Schools model, focused on developing employability skills in young people, represents a disruptive attempt at educational innovation. Through a documentary analysis of foundational documents, interviews with the model's architects and case studies of five Studio Schools, we map the tensions between theoretical conceptualisations of the model and the messy realities of implementing it. We found that the schools faced a wide range of challenges related particularly to local inter‐school competition, centralised accountability measures and structural assumptions about the 'gold educational standard'. When facing these challenges, the course of least resistance for the schools was an iterative abandonment of the distinctive aspects of the Studio Schools model and a move back towards mainstream approaches to schooling. This process of institutional homogenisation is discussed through the lens of neo‐institutional theory, with the challenges schools faced and their trajectories framed in terms of coercive, mimetic and normative isomorphism. We argue that the use of isomorphism as a heuristic device provides important insight into the process of educational innovation in an educational system that combines competition and the risk of market failure with coercive accountability measures and embedded assumptions about the 'gold standard' schooling pathway.